1976
DOI: 10.1063/1.432433
|View full text |Cite
|
Sign up to set email alerts
|

Configuration interaction calculations of low-lying electronic states of O2,O2+, and O22+

Abstract: Minimal basis full valence CI calculations of potential curves are reported for more than 300 low-lying states of O2, O+2, and O2+2. A large number of new bound states of O+2 and some metastable states of O2+2 are predicted, and from a comparison with known states of O2 and O+2, predictions are made for the spectroscopic constants of the as yet experimentally unknown states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1
3

Year Published

1981
1981
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(66 citation statements)
references
References 37 publications
5
57
1
3
Order By: Relevance
“…Therefore, if a vibrational level of an ionic state coincides with an autoionization state which has an appropriate absorption cross section from the ground state, the TPES signal of the level may be observed even if the Franck-Condon factor for the direct PES transition is too small. Configuration interaction calculations of low-lying electronic states of O 2 ϩ were reported by Beebe et al 6 They suggested that in addition to the X 2 ⌸ g , A 2 ⌸ u and a 4 ⌸ u states, four other bound states which dissociate to the first dissociation limit are possible, that is, 2 ⌺ u ϩ , 4 ⌺ g ϩ , 6 ⌺ u ϩ and 4 ⌸ g , and they gave predicted spectroscopic constants (T e ,r e ,w e ,D e ) of these states. Yeager et al 7 calculated the ionization energies and the potential curves of seven lower states of O 2 ϩ .…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Therefore, if a vibrational level of an ionic state coincides with an autoionization state which has an appropriate absorption cross section from the ground state, the TPES signal of the level may be observed even if the Franck-Condon factor for the direct PES transition is too small. Configuration interaction calculations of low-lying electronic states of O 2 ϩ were reported by Beebe et al 6 They suggested that in addition to the X 2 ⌸ g , A 2 ⌸ u and a 4 ⌸ u states, four other bound states which dissociate to the first dissociation limit are possible, that is, 2 ⌺ u ϩ , 4 ⌺ g ϩ , 6 ⌺ u ϩ and 4 ⌸ g , and they gave predicted spectroscopic constants (T e ,r e ,w e ,D e ) of these states. Yeager et al 7 calculated the ionization energies and the potential curves of seven lower states of O 2 ϩ .…”
Section: Introductionmentioning
confidence: 82%
“…Possible states which may arise from this limit are 2,4,6 ⌺ g,u ϩ , 2,4,6 ⌸ g,u . The potential energy curves for these states were calculated by Beebe et al 6 The 4 ⌸ g state has been well investigated by many authors. [21][22][23][24][25] We cannot recognize, in the present experiment, the 4 ⌸ g state which is predicted to have a shallow minimum.…”
Section: New Statesmentioning
confidence: 99%
“…78 Being an open shell molecule, the multiplicaties for electronic states of 02 and its cation are complicated. The description of excitred 02 states, especially in the innervalence region (19-30 eV) at energies above the dissociation energy of 02 (18.733 eV), requires extensive configuration interaction (CIs).…”
Section: Rotational-resolved Pfi-pe Bands Formentioning
confidence: 99%
“…The potential energy curves for the neutral molecule and molecular ions were found in Refs. [32][33][34][35][36]. As for the nitrogen molecule, we plot the classically calculated traces on top of the experimental spectra for the O 2+ + O 2+ channel.…”
Section: B Oxygenmentioning
confidence: 99%